ALIMENTOS INDUSTRIALIZADOS FONTES DE SÓDIO UTILIZADOS NO PREPARO DE REFEIÇÕES EM RESTAURANTES COMERCIAIS DE CHAPECÓ-SC - Lúcia Chaise Borjes; Fernan Junior Tasca; Patrícia Eliza Zamprogna (Universidade do Estado do Rio de Janeiro, 2014)
Given the high consumption of meals outside the home and use ofprocessed foods high in sodium in the preparation of these meals,combined with the global concern of increased blood pressure andits associated risks, this study aimed to estimate the amount ofsodium and the contribution of industrial foods in the per capitaquantification of this nutrient in the meals offered by commercialpay-by-weight restaurants in Chapecó-SC, Brazil. Data werecollected in four commercial restaurants in March 2011. Duringone day in each restaurant, we verified the nutritional informationof sodium in all processed food sources of this nutrient used in thelunch served by the restaurants.. The average quantities of productsused per week, as well as the average number of meals producedwere informed by those responsible for production. The resultsshowed that the average per capita amount of sodium found forlunch was 1.742 g in four restaurants. Of these, 52.25% (0.910 gsodium) were from industrial food sources of sodium, and 47.7%(0.805 g sodium) from total salt addition (used in the preparationand added by consumers at the dinner table). It should be notedthat the intrinsic sodium in foods was not considered. It can beseen that the estimated amount of sodium contained in the mealsin the four studied restaurants exceeds more than twice the amountrecommended for lunch, which is only 0.700 g sodium. Given theabove, it is evident that the food production units should reduce theuse of these foods in the menu, so as to to offer meals nutritionallyadequate with respect to salt and sodium. Compulsory hiring ofa professional nutritionist in these establishments would be animprovement in the quality of consumers' health. DOI 10.12957/demetra.2014.7249